Replant : how a dying church can grow again - DeVine, Mark, 1960-; Patrick, Darrin, 1970-2020. (Colorado Springs, CO : David C Cook, 2014)
Grow where you're replanted. Today's spiritual landscape is littered with churches on their last legs, forcing us to reconsider how we keep the body of Christ alive and strong. The solution, according to visionary pastors Darrin Patrick and Mark DeVine, is to infuse new blood into the body by seeking God's presence and guidance. Avoiding cookie-cutter steps or how-to formulas, Replant describes the story of a church resurrection -- a story that offers a multitude of divinely inspired and practical possibilities for churches. The result is a harvest of ideas on how to promote new church growth. Discover a revitalized openness to churches merging with other congregations, changing leadership, and harvesting fresh spiritual fruit, inviting us all to rethink how churches not only survive, but thrive. - Back cover.
The making of a madman -- Feeling out the faded glory -- Dissecting dysfunction -- The devil's workshop -- Assisted suicide -- I'm not the man -- Merger mania -- The seed dies -- Decisions and dreams -- Giving up control -- Answering the divine call -- Two churches become one -- Appendices. "Rocks that cry out, " or, bodies and buildings ; The open business meeting.
Includes bibliographical references.
Keywords: Church growth; Church development, New; Evangelistic work